ENaCT: A Framework for Action-based Analytics of Critical Thinking (International Conference on Computers in Education, 2020)
Critical thinking (CT) is an important 21st-century skill. In this paper we propose a new framework – Embodied Narratives of Critical Thinking (ENaCT) – to conceptualise the learning of CT, as well as analytics to assess CT, in a technology-enhanced environment. In the context of a CT activity, this position paper bridges the perspectives of embodied cognition, aligning actions that constitute learning, with learning analytics approaches, to measure and build embodied narratives of the learning process. We illustrate the components of this new framework through a preliminary interface design conceptualised for the learning of CT within an online reading platform. Applicability of the framework and future research agenda are discussed.